Early Aggressive Treatment Approaches for Multiple Sclerosis - Simpson, Alexandra; Mowry, Ellen M.; Newsome, Scott D. (Current treatment options in neurology, 2021)
Purpose of review This review presents a comprehensive analysis of the current high-efficacy disease-modifying therapies (DMTs) available for treatment of multiple sclerosis (MS). We discuss the existing approved and emerging therapeutics in patients with relapsing and progressive forms of MS using data from clinical trials and observational studies. Treatment considerations in pediatric and pregnant populations are also reviewed. Finally, we discuss the treatment paradigms of the escalation and early aggressive approaches to treatment of MS, with review of ongoing clinical trials to compare these approaches. Recent findings Natalizumab has shown promising data on efficacy in not only randomized trials but also observational studies when compared with placebo, the injectable DMTs, and fingolimod. The anti-CD20 B cell depleting therapies (rituximab, ocrelizumab, and ofatumumab) have also demonstrated superiority in randomized clinical trials compared to their comparator group (placebo, interferon, and teriflunomide, respectively) and rituximab has shown in observational studies to be more effective than older injectable therapies and some of the oral therapies. Alemtuzumab has shown good efficacy in randomized controlled trials and observational studies yet has several potentially severe side effects limiting its use. Mitoxantrone has similarly demonstrated significant reduction in new disease activity compared to placebo but is rarely used due to its severe side effects. Cladribine is an oral DMT often grouped in discussion with other higher efficacy DMTs but may be slightly less effective than the other therapies described in this review. Many emerging targets for therapeutic intervention are currently under investigation that may prove to be beneficial in early aggressive MS, including autologous hematopoietic stem cell transplantation. Summary Traditionally, MS has been treated with an escalation approach, starting patients on a modestly effective DMT and subsequently escalating to a higher efficacy DMT when there is evidence of clinical and/or radiologic breakthrough activity. With the development of higher efficacy therapies and emerging data showing the potential positive long-term impact of these therapies when started earlier in the disease course, many clinicians have shifted to an early aggressive treatment approach in which patients are initially started on a higher efficacy DMT. Two clinical trials, the TRaditional versus Early Aggressive Therapy for MS (TREAT-MS) trial and the Determining the Effectiveness of earLy Intensive Versus Escalation approaches for the treatment of Relapsing-remitting MS (DELIVER-MS) trial, aim to directly compare these treatment strategies and their impact on clinical and radiologic outcomes.